Inhibition of Alanine and Aspartate Aminotransferases by B-Nitropropionic Acid - Hassan M.Y. Osman (Journal of High Institute of Public Health, 2007)
The inhibition of serum alanine and aspartate aminotransferases (SALT and SAST) by b nitropropionic acid (bNPA), toxic metabolite of some fungi higher plants) in vitro was studied. The results indicated that both SALT and SAST were competitively inhibited by bNPA and the enzymes recovered their original activity by dialysis, indicating that the inhibitory effect of bNPA is reversible. The inhibition of both SALT and SAST by bNPA was found to be slow and showed the characteristic of a first order reaction up to 30 minutes. The rate constants characterizing this inhibition, namely: the binding constant (KB) (90 uM and 225 uM for SALT and SAST, respectively) and bimolecular velocity of inhibition ki (666 and 714 (M min)-1 for SALT and SAST, respectively were determined. Kn (rate of nitrification of the enzymes) for SALT and SAST were 0.06/min and 0.18/min, respectively.